DEVELOPMENT OF MATHEMATICAL LITERACY PROBLEMS IN THE MINIMUM COMPETENCY ASSESSMENT (AKM) FOR CLASS VIII STUDENTS OF JUNIOR HIGH SCHOOL - Zuhro, Syifa Ul Fatimatuz; Jaelani, Anton (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
The replacement of the National Examination into the 2021 National Assessment which consists of 3 elements, namely AKM, character survey, and learning environment survey. The Minimum Competency Assessment (AKM) focuses on students' ability to master reading literacy and numeracy literacy so that students are required to have good mathematical literacy skills. This research is a Research and Development study which aims to (1) produce mathematical literacy questions on the minimum competency assessment (produce valid and reliable mathematical literacy questions in the minimum competency assessment (AKM) for class VIII SMP students in the form of an essay test.; (2) Knowing students' responses to the mathematical literacy problems being developed. This research was carried out in class VIII H of SMP N 9 Purwokerto, by carrying out one product trial phase for 80 minutes. The AKM standards used in developing mathematical literacy questions contain three components, namely content, context and cognitive processes, with material content limitations including algebra, plane figures, arithmetic rows and series, data presentation and comparison. The instruments in this research used mathematical literacy question sheets, teacher response questionnaires, and validator sheets. The model used in this development is the Thiagaradjan, and Semmel & Semmel 4-D model which consists of four stages; (1) Define; (2) Design; (3) Develop; and (4) Disseminate. However, this research has only reached the 3D or Develop stage. The limit of question content is middle school material for grades 7 and 8. The results of the research show that the level of validity of mathematical literacy questions in the Minimum Competency Assessment (AKM) has the criteria of "valid" because it meets the requirements of â‰¥75 with a percentage per item reaching more than of 75% and the overall percentage obtained a score of 81%. The reliability calculation results for question package A are 0.67 and question package B is 0.65, so these two questions can be said to be "reliable". Apart from that, students' responses to mathematical literacy questions showed "good" criteria with a percentage of 82%, this means that mathematical literacy questions made students interested in the questions being developed.Keywords: Minimum Competency, Assessment (AKM), Mathematical Literacy, 4D Model, SMP N 9 Purwokerto